2023
DOI: 10.1097/lvt.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, prehabilitation intervention to maximize early recovery (PRIMER) in liver transplantation

Abstract: Frailty and impaired functional status are associated with adverse outcomes on the liver transplant (LT) waitlist and after transplantation. Prehabilitation prior to LT has rarely been tested. We conducted a 2-arm patient-randomized pilot trial to evaluate the feasibility and efficacy of a 14-week behavioral intervention to promote physical activity prior to LT. Thirty patients were randomized 2:1 to intervention (n = 20) versus control (n = 10). The intervention arm received financial incentives and text-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…A recent systematic review on prehabilitation in patients awaiting LT did not detect an impact on adverse clinical outcomes including mortality due to sparse data ( 33 ). This lack of findings might also be confounded by not having identified the beneficial exercise intervention or prehabilitation program so far in these patients ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on prehabilitation in patients awaiting LT did not detect an impact on adverse clinical outcomes including mortality due to sparse data ( 33 ). This lack of findings might also be confounded by not having identified the beneficial exercise intervention or prehabilitation program so far in these patients ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that nutrition alone is insufficient to improve functional status in patients with CLD, malnutrition, and frailty[ 1 ]. Recent studies on prehabilitation in patients preparing for liver transplantation have shown that interventions such as increased daily step count, and introduction of strength exercises is safe, feasible, and can improve aerobic and functional capacity[ 48 , 49 ].…”
Section: General Nutrition Recommendations For Patients With Liver Di...mentioning
confidence: 99%
“…Home-based protocols are more accessible for participants, where exercise programming often requires no additional equipment and can be performed with minimal or even no supervision. However, home-based interventions also present challenges as well, including lower exercise adherence rates than traditional facility-based programs, perhaps owing to low rates of intrinsic motivation in the absence of in-person accountability, although this has been addressed by having a supervised portion of an in-home digital therapeutic-based intervention 14,15,17 . Despite these limitations, home-based exercise programs can lead to clinically meaningful improvement in both frailty and physical performance and should be considered in the right clinical setting, especially if time, cost, or exercise resource access barriers are identified before exercise prescription development (Figure 1).…”
Section: Exercise Prescription For Individuals With Advcldmentioning
confidence: 99%